The Relationship Between Self-Compassion and Self-Harm Behaviors Among Early Adolescents in the Agricultural Region of Jember Regency - Fitria, Yeni; Azizah, Lia; Deviantony, Fitrio; Dewi, Erti Ikhtiarini; Kurniyawan, Enggal Hadi (Journal of Nursing Science Update (JNSU), 2024)
Self-harm behaviour is prevalent among adolescents, particularly during early adolescence, a period characterized by significant pressures and demands. This study examines self-compassion as a potential coping mechanism to mitigate self-harm in early adolescents, specifically within the agricultural region of Jember Regency. The research employed a correlational design within a cross-sectional framework comprising 376 junior high school students. The participants were assessed for self-compassion utilizing the Self-Compassion Scale (SCS) and for self-harm behaviour through the Deliberate Self-Harm Inventory (DSHI). The findings indicate that 67.6% of participants exhibited moderate levels of self-compassion, while 84.8% reported low instances of self-harm behaviour. A statistically significant relationship was identified (p = 0.001), revealing a low negative correlation (r = -0.200), which suggests that higher levels of self-compassion are associated with reduced self-harm. In conclusion, the results underscore the importance of promoting self-compassion programs within schools and among healthcare professionals as a means to address self-harm in adolescents.